2016
DOI: 10.1212/wnl.0000000000003147
|View full text |Cite
|
Sign up to set email alerts
|

The child neurology clinical workforce in 2015

Abstract: Objectives: More than a decade has passed since the last major workforce survey of child neurologists in the United States; thus, a reassessment of the child neurology workforce is needed, along with an inaugural assessment of a new related field, neurodevelopmental disabilities. Methods:The American Academy of Pediatrics and the Child Neurology Society conducted an electronic survey in 2015 of child neurologists and neurodevelopmental disabilities specialists.Results: The majority of respondents participate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Since 2009, several studies and surveys of the child neurology workforce have demonstrated shortages of pediatric neurologists. 7,19 Therefore, innovative models of health care delivery must have a strong emphasis on real-time physician education in a coordinated team-based approach. Integration of QI into such models makes them more meaningful and clinically relevant for physicians and can translate into sustainable practice change over time.…”
Section: T a B L Ementioning
confidence: 99%
See 1 more Smart Citation
“…Since 2009, several studies and surveys of the child neurology workforce have demonstrated shortages of pediatric neurologists. 7,19 Therefore, innovative models of health care delivery must have a strong emphasis on real-time physician education in a coordinated team-based approach. Integration of QI into such models makes them more meaningful and clinically relevant for physicians and can translate into sustainable practice change over time.…”
Section: T a B L Ementioning
confidence: 99%
“…Epilepsy remains one of the most common reasons for referral to a pediatric neurologist. 7 Unfortunately, there is an existing deficiency in the number of pediatric neurologists (estimated to be at least 20% below the national need), often resulting in limited access to care for CYE, especially in rural and underserved communities. 8,9 Health care delivery system use of telemedicine technology is one way to improve subspecialty care access.…”
Section: Introductionmentioning
confidence: 99%
“…This paralleled our institutional data that identified an increasing emphasis on interpersonal relationships and applicants perceived “personality fit” with residents based on their interview day experience. Our survey respondents were generally representative of the child neurology workforce with an increasing representation of females 10 , 11 , 12 and number of DO degrees over time. 12 Our respondents had a higher representation of MD/PhD degrees than recent workforce numbers, which have demonstrated an overall decrease in MD/PhD degrees over time.…”
Section: Discussionmentioning
confidence: 99%
“…There was a higher predominance of physicians with MD/PhD degrees (5.9%) in the practicing physicians than trainees and trend for increasing representation of trainees with DO degrees (1.7% practicing physicians and 12.6% trainees). 12 Given the changes in applicant demographics and educational backgrounds, we questioned whether this his created a shift in training priorities.…”
Section: Introductionmentioning
confidence: 99%
“…The prospects for more child neurologists in the United States seemed ominous in 2005 11 and appear to have been realized 12 . In contrast, a certain oversupply was reported from Canada 13 .…”
Section: Discussionmentioning
confidence: 99%